Analisis Terhadap Minat Berwirausaha Mahasiswa Dari Faktor Pendidikan Kewirausahaan, Motivasi Berwirausaha dan Lingkungan Keluarga - Nurhaida Nurhaida (Mahesa Research Center, 2021)
This study aims to determine the effect of entrepreneurship education, entrepreneurial motivation and family environment on students' interest in entrepreneurship. This research was conducted at the Mandiri Bina Prestasi Polytechnic with a population of 178 students who had taken entrepreneurship courses. By using the Slovin formula, a sample of 64 students was obtained. In use in this research is a survey approach, the type of research used is descriptive quantitative. The technique of collecting data by means of interviews, distributing questionnaires and studying documentation. The data analysis model used multiple linear regression analysis, tested with a confidence level of 95%. To test the hypothesis, the simultaneous test (F test), partial test (t test) and determination coefficient measurement (R2 test) were carried out.The test results simultaneously have entrepreneurial education, entrepreneurial motivation and family environment have a significant effect on the entrepreneurial interest of Bina Prestasi Polytechnic students. Partially, entrepreneurship education has a significant effect on the entrepreneurial interest of the Mandiri Bina Prestasi Polytechnic students, entrepreneurial motivation has a significant effect on the entrepreneurial interest of the Mandiri Bina Prestasi Polytechnic students, and the family environment has a significant effect on the entrepreneurial interest of the Mandiri Bina Prestasi Polytechnic students. The coefficient of determination R Square is 0.574. This means that 57.40% of the variables of entrepreneurship education, entrepreneurial motivation and the family environment have the ability to explain their influence on interest in entrepreneurship. while the rest is influenced by other independent variables not examined in this study.